THERMODYNAMIC ANALYSIS OF RECUPERATIVE AND REHEAT BASED ON ORGANIC RANKINE CYCLE FOR HIGH-TEMPERATURE WASTE HEAT RECOVERY - Fara Nabilah Sakina; Habibatu Nihayah; Teguh Hady Ariwibowo; Lohdy Diana (Jurnal Rekayasa Mesin, 2023)
Heat recovery from available waste heat is an essential method in renewable energy processes due to the ability to generate electricity by using Organic Rankine Cycles (ORC). The process model is developed with the Cycle Tempo software. Fluid properties were analyzed with Reference Fluid Properties (REFPROP) software. This research presents a thermodynamic comparison of the Basic Organic Rankine Cycle (BORC) and Recuperative Organic Rankine Cycle (RORC) for waste heat recovery applications using pure refrigerants R-141b, R-245fa, R-123, and R-21. By performing simulations for heat source high-temperatures ranging from 160 to 200 °C. The comparison between BORC and RORC performance parameters and refrigerant properties was evaluated on the heat source temperature. Research shows that RORC produces higher thermal efficiency but has lower irreversibility than BORC. RORC has a maximum thermal efficiency of 12.67%, and BORC has a thermal efficiency of 11.49% for refrigerant R-141b at a flue gas temperature of 160 °C. The thermal efficiency of the ORC increases as the temperature of the heat source increases.